Analysis of the Influence of Exports, Imports, Foreign Investment and Labor on Indonesia's GDP - Linstrie Lara Ria; Andrie Elia; Alexandra Hukom (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
Gross Domestic Product (GDP) is a measure of country’s economic production conditions. Estimates of economic growth in the coming year in a country have an important role, among others, as a benchmark for companies in determining production plans in the coming year, and the basis for the design of government spending. This study aims to determine and analyze the effect of Exports, Imports, Foreign Investment, and Labor on Indonesia’s Gross Domestic Product. The tyoe of research used is descriptive quatitative, and the data in this study were obtained from the Central Statistics Agency (BPS). The analysis technique uses panel data regression analysis method and is assisted by using the Eviews 11 program in calculating the data. The result of panel data regression analysis in this study show that exports have a positive and insignificant effect on Indonesia’s Gross Domestic Product. Imports have a negative and insignificant effect on Indonesia’s Gross Domestic Product. Foreign Investment has a negative and insignificant effect on Indonesia’s Gross Domestic Product. Labor has a positive and significant effect on Indonesia’s Gross Domestic Product.